Gas sensing properties of conducting polymer/Au-loaded ZnO nanoparticle composite materials at room temperature - Viruntachar Kruefu (2018)
© 2014, Kruefu et al.; licensee Springer. In this work, a new poly (3-hexylthiophene):1.00 mol% Au-loaded zinc oxide nanoparticles (P3HT:Au/ZnO NPs) hybrid sensor is developed and systematically studied for ammonia sensing applications. The 1.00 mol% Au/ZnO NPs were synthesized by a one-step flame spray pyrolysis (FSP) process and mixed with P3HT at different mixing ratios (1:1, 2:1, 3:1, 4:1, and 1:2) before drop casting on an Al 2 O 3 substrate with interdigitated gold electrodes to form thick film sensors. Particle characterizations by X-ray diffraction (XRD), nitrogen adsorption analysis, and high-resolution transmission electron microscopy (HR-TEM) showed highly crystalline ZnO nanoparticles (5 to 15 nm) loaded with ultrafine Au nanoparticles (1 to 2 nm). Film characterizations by XRD, field-emission scanning electron microscopy (FE-SEM), energy-dispersive X-ray (EDX) spectroscopy, and atomic force microscopy (AFM) revealed the presence of P3HT/ZnO mixed phases and porous nanoparticle structures in the composite thick film. The gas sensing properties of P3HT:1.00 mol% Au/ZnO NPs composite sensors were studied for reducing and oxidizing gases (NH 3 , C 2 H 5 OH, CO, H 2 S, NO 2 , and H 2 O) at room temperature. It was found that the composite film with 4:1 of P3HT:1.00 mol% Au/ZnO NPs exhibited the best NH 3 sensing performances with high response (approximately 32 to 1,000 ppm of NH 3 ), fast response time (4.2 s), and high selectivity at room temperature. Plausible mechanisms explaining the enhanced NH 3 response by composite films were discussed.